APAKAH FAKTOR EKSTERNAL MEMPREDIKSI UNDERPRICING LEBIH BAIK DIBANDINGKAN FAKTOR INTERNAL? STUDI INITIAL PUBLIK OFFERING DI BEI TAHUN 2009-2017 - Saefudin, Saefudin; Gunarsih, Tri (FEB Universitas Sam Ratulangi Manado, 2020)
Underpricing is a phenomenon that still occurs in the Indonesian capital market, where the offering price of shares in the primary market is lower than the opening price or closing price on the first day on the secondary market. This study aims to examine the effect of Return On Assets (ROA), Debt to Equity Ratio (DER), company size, underwriter reputation, age, and interest rates on the underpricing of shares in companies’s Initial Public Offering (IPO) listing on the Indonesia Stock Exchange (BEI) in 2009 to 2017. The population in this study are companies that conduct IPOs on the BEI period 2009 to 2017. The sample selection in this study uses a purposive sampling method, based on certain criteria. The sample in this study were 183 underpricing companies from 205 companies conducting IPO in the period 2009 to 2017. The data used in this study used secondary data. The multiple regression analysis was implemented in this study. The results showed that DER, company size, and underwriter reputation did not significantly influence underpricing. While ROA, age and interest rates have a significant negative effect on underpricing. In this study, investors consider ROA, age, interest rates compared to DER, company size, and the reputation of the underwriter to invest in companies that make an IPO.Keywords: Underpricing, Initial Public Offering, and Indonesian Stock Exchange.